Fulfillment of the Right to Education in Border Areas: A Juridical Review of the Implementation of the Right to Basic Education in Temajuk District, Sambas Regency - Itasari, Endah Rantau; Anhari, Radifan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study explores the fulfillment of the right to basic education in Temajuk Subdistrict, a border area in West Kalimantan, Indonesia. Despite strong legal frameworks such as the 1945 Constitution, Law No. 20 of 2003, and international commitments under the ICESCR, the actual implementation faces significant challenges. Using a combined normative and empirical juridical approach, the research analyzes regulations and incorporates interviews with local stakeholders. Findings show limited educational facilities serving approximately 2,687 residents, poor infrastructure, inadequate supporting resources, and difficult access due to challenging geography and transportation. High teacher turnover and a curriculum misaligned with local needs further hinder education quality. Additionally, the lack of specific regional regulations and weak coordination among agencies obstruct effective policy execution. The study highlights the urgent need for targeted government intervention, improved infrastructure, better teacher support, localized curricula, and strengthened inter-agency collaboration. Enhancing government responsiveness and involving local communities are essential to achieving equitable, quality education in Temajuk and fulfilling Indonesia’s constitutional and international educational obligations in border areas.